Sheep recombinant IGF-1 promotes organ-specific growth in fetal sheep - Stremming, J; White, A; Donthi, A; Batt, DG; Hetrick, B; Chang, EI; Wesolowski, SR; Seefeldt, MB; McCurdy, CE; Rozance, PJ; Brown, LD (Frontiers in Physiology, 2022)
IGF-1 is a critical fetal growth-promoting hormone. Experimental infusion of an IGF-1 analog, human recombinant LR3 IGF-1, into late gestation fetal sheep increased fetal organ growth and skeletal muscle myoblast proliferation. However, LR3 IGF-1 has a low affinity for IGF binding proteins (IGFBP), thus reducing physiologic regulation of IGF-1 bioavailability. The peptide sequences for LR3 IGF-1 and sheep IGF-1 also differ. To overcome these limitations with LR3 IGF-1, we developed an ovine (sheep) specific recombinant IGF-1 (oIGF-1) and tested its effect on growth in fetal sheep. First, we measured in vitro myoblast proliferation in response to oIGF-1. Second, we examined anabolic signaling pathways from serial skeletal muscle biopsies in fetal sheep that received oIGF-1 or saline infusion for two hours. Finally, we measured the effect of fetal oIGF-1 infusion versus saline infusion (SAL) for one week on fetal body and organ growth, in vivo myoblast proliferation, skeletal muscle fractional protein synthetic rate, IGFBP expression in skeletal muscle and liver, and IGF-1 signaling pathways in skeletal muscle. Using this approach, we showed that oIGF-1 stimulated myoblast proliferation in vitro. When infused for one week, oIGF-1 increased organ growth of the heart, kidney, spleen, and adrenal glands and stimulated skeletal myoblast proliferation compared to SAL without increasing muscle fractional synthetic rate or hindlimb muscle mass. Hepatic and muscular gene expression of IGFBPs 1-3 was similar between oIGF-1 and SAL. We conclude that oIGF-1 promotes tissue and organ-specific growth in the normal sheep fetus.